Experimental evidences and theoretical calculations on phenanthrene degradation in a solar-light-driven photocatalysis system using silica aerogel supported TiO2 nanoparticles: Insights into reactive sites and energy evolution - Ji, Haodong; Liu, Wen; Fengbin Sun; Taobo Huang; Long Chen; Yue Liu; Juanjuan Qi; Chenghan Xie; Zhao, Dongye (Chemical Engineering Journal, 2021)
Quantitative identification on reactive sites of target organic molecule during photocatalysis can help to get deep insight into the pollutant degradation pathway and energy evolution process. In this study, a new class of silica aerogel supported TiO2 (TiO2/SiO2) photocatalysts were fabricated via a two-step approach, and applied for adsorption and photocatalytic degradation of phenanthrene. Anatase crystalline structure was formed upon calcination at 400 and 600 °C, while mixed crystal interphases of anatase and rutile were generated at 800 °C (anatase:rutile = 0.67:0.33). The higher calcination temperature resulted in better crystallinity of TiO2, higher photocatalytic activity, and reduced adsorption affinity toward phenanthrene. TiO2/SiO2-800 (TiO2/SiO2 calcined at 800 °C) showed minimal phenanthrene uptake ( 5.2%) but the strongest photocatalytic activity, and it was able to completely degrade phenanthrene within 3 h. The SiO2 aerogel component in the composite enabled the pre-concentration of phenanthrene on the photoactive sites, while the nanoscale mixed-phases of anatase and rutile of TiO2/SiO2-800 act as an efficient transfer medium for photo-induced charge carriers. Moreover, the formed Ti–O–Si linkage in TiO2/SiO2-800 induced formation of Ti3+ under solar light irradiation, promoting photoexcited electron trap and separation of electron-hole pairs. Based on the degraded phenanthrene intermediates/products, theoretical calculations according to the density functional theory (DFT) reveal that the atoms of phenanthrene with high electrophilic Fukui index (f -) are the most reactive sites towards the radicals. Potential energy surface profile for phenanthrene degradation further reveals the intermediates energy evaluation via radicals attack.
Keywords: Density functional theory; Organic pollutants; Photocatalysis; Reactive sites; TiO nanoparticles